A yttrium-antimony co-doped IZTO sputtering target and a preparation method thereof

CN122977833APending Publication Date: 2026-10-27LUOYANG JINGLIAN OPTOELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611101984.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]针对现有IZTO靶材氧空位浓度高、致密度低、锌挥发损耗大、配套薄膜器件稳定性差等缺陷,本发明提供一种钇锑共掺杂IZTO溅射靶材及其制备方法

Benefits of technology

(1)Y3+的晶格位点占据畸变作用与Sb5+的电子补偿作用相互配合,搭配三段烧结中高温致密补氧段的富氧氛围,实现了对氧空位的双重抑制。采用本发明靶材磁控溅射制备的IZTO薄膜晶体管,其饱和迁移率较常规IZTO靶材制备的薄膜显著提升,3600s光照负偏压测试下的阈值电压漂移大幅减小。这意味着在超高分辨率(如8K及以上)AMOLED等高端显示应用中,采用本发明靶材制备的像素阵列能够在长时间高亮度工作条件下保持稳定的开关特性,有效避免因阈值漂移导致的亮度不均和残影问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784777710766-000001
    Figure REF-OBJ-1784777710766-000001
Patent Text Reader

Abstract

The application discloses a yttrium-antimony co-doped IZTO sputtering target material and a preparation method thereof, and belongs to the technical field of transparent conductive oxide target material preparation. The target material base is composed of ternary oxides of In2O3, ZnO and SnO2, and is doped with Y2O3 and Sb2O5; in terms of atomic percentage, In is 22at.% to 26at.%, Zn is 52at.% to 58at.%, Sn is 18at.% to 22at.%, and the sum of the three is 100at.%; taking the total atomic percentage of the three as a reference, Y is 0.2at.% to 0.7at.%, and Sb is 0.2at.% to 0.5at.%. The preparation method comprises ZnO surface coating pretreatment, hierarchical step-by-step wet pulping, spray granulation and cold isostatic pressing forming, and three-stage sintering. Through Y-Sb synergistic doping and segmented oxygen control sintering, the target material has high density, low oxygen vacancy concentration and small zinc volatilization loss, the sputtering thin film has high mobility and good device stability, the process has strong compatibility and low cost, and the application is suitable for fields of 8K high-brush AMOLED and perovskite stacked batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of transparent conductive oxide target preparation technology, specifically to a yttrium antimony co-doped IZTO sputtering target and its preparation method, which is particularly suitable for indium zinc tin oxide (IZTO) magnetron sputtering targets for ultra-high resolution (e.g., 8K and above) high-frequency driving thin film transistors and perovskite tandem battery channel / transparent conductive layer. Background Technology

[0002] IGZO (indium gallium zinc oxide) is currently the mainstream material in the field of oxide semiconductors and has been commercially applied in display drivers. However, the upper limit of carrier mobility for IGZO is only 40 cm⁻¹. 2 The current speed is around / V·s, which is insufficient to meet the driving requirements of ultra-high-definition display panels with a refresh rate of 120Hz and above. IZTO (Indium Zinc Tin Oxide) relies on In 3+ Sn 4+ The 5s orbital overlap effect of IZTO, with a theoretical mobility significantly superior to IGZO, is considered a core material for next-generation high-performance active layers. However, the production and application of existing commercial IZTO targets still face many technical challenges.

[0003] First, the significant difference in sintering activity between powders is the primary factor limiting the quality of IZTO targets. During the mixing and sintering process of In₂O₃, ZnO, and SnO₂ oxide powders, Zn readily volatilizes at high temperatures, while Sn is prone to localized segregation, leading to a large number of oxygen vacancy defects within the target material. These defects are directly inherited by the sputtered film, increasing the defect state density. TFT devices fabricated with this type of target material exhibit threshold voltage drift exceeding 1.2V after negative bias testing under illumination, severely impacting the long-term operational stability of the pixel array.

[0004] Secondly, conventional atmospheric pressure sintering processes struggle to achieve high densification of the target material. IZTO targets prepared using traditional methods have a relative density of only 94%–97%, leaving numerous closed pores within the preform. These pores can induce arc discharge during magnetron sputtering and easily eject large particles, leading to pinhole defects on the film surface and resulting in a mass production yield of less than 82% for displays and photovoltaic devices. While hot isostatic pressing (HIP) can improve density, its equipment investment is enormous, making it unsuitable for the mass production demands of large-size targets.

[0005] Furthermore, the non-gradient temperature-controlled sintering method leads to severe grain size differentiation in the target material. Under isothermal sintering conditions, abnormal grain growth is prone to occur in local areas of the target material, with grain sizes reaching over 15 μm. This grain size inhomogeneity results in significant differences in the conductive pathways of different regions of the target material. The sheet resistance difference of the film sputtered from the same target exceeds 12%, ultimately causing excessive dispersion in the electrical performance of batch devices.

[0006] Furthermore, conventional sintering lacks atmosphere protection measures. Within the sintering temperature range of 800~1300℃, ZnO continues to decompose and volatilize, causing the actual atomic ratio of Zn in the finished target material to deviate from the designed ratio. Manufacturers have to repeatedly calibrate the ratio of powder raw materials for each batch, but even so, the zinc loss rate during the sintering process still exceeds 11%, significantly increasing raw material costs.

[0007] To address the aforementioned issues, existing improvement solutions are mostly single-strategy approaches, such as controlling powder particle size, performing micro-doping of a single component, or simply increasing the sintering temperature. These methods can only improve density to a certain extent and cannot simultaneously solve the three interconnected technical problems of oxygen vacancy enrichment, zinc volatilization, and grain coarsening. Furthermore, the mainstream doping systems in the industry mostly use Ga or Al elements, but gallium oxide raw materials are scarce and have high procurement costs, and Ga... 3+ It compresses electron transport orbits, which in turn leads to a significant decrease in the mobility of charge carriers in thin films. Summary of the Invention

[0008] To address the shortcomings of existing IZTO sputtering targets, such as high oxygen vacancy concentration, low density, significant zinc volatilization loss, and poor stability of associated thin-film devices, this invention provides a yttrium-antimony co-doped IZTO sputtering target and its preparation method. This invention, without reducing the thin film carrier mobility, suppresses lattice oxygen vacancy generation, significantly reduces high-temperature zinc volatilization, and achieves uniform grain refinement, resulting in a target relative density of no less than 99.6% and a sputtered thin film mobility of no less than 45 cm⁻¹. 2 / V·s, the threshold voltage drift under negative bias of 3600s illumination does not exceed 0.15V, which can meet the industrial mass production needs of large-size sputtering targets.

[0009] To achieve the above objectives, the specific solution adopted by the present invention is as follows: In a first aspect, the present invention provides a yttrium-antimony co-doped IZTO sputtering target, wherein the matrix of the target is composed of a ternary oxide of In2O3, ZnO and SnO2, and is doped with Y2O3 and Sb2O5. In terms of atomic percentage, the target material contains 22 at.%~26 at.%, 52 at.%~58 at.%, and 18 at.%~22 at.%, with the sum of In, Zn, and Sn being 100 at.%. Based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.2 at.% to 0.7 at.%, the atomic percentage of Sb is 0.2 at.% to 0.5 at.%, and the sum of the atomic percentages of Y and Sb is 0.4 at.% to 1.2 at.%.

[0010] Furthermore, in terms of atomic percentage, the target material contains 24 at.%, 55 at.%, and 20 at.%, with the sum of the three being 100 at.%; based on the total atomic percentage of the three, the atomic percentage of Y is 0.45 at.%, and the atomic percentage of Sb is 0.3 at.%.

[0011] Furthermore, the target material meets the following microstructure and performance indicators: relative theoretical density ≥99.6%, internal closed porosity ≤0.15%, average grain size of 1.2μm~3.5μm, and lattice oxygen vacancy concentration. Furthermore, the atomic composition fluctuations of In, Zn, and Sn across the entire target area do not exceed ±0.3 at.%.

[0012] Furthermore, the purity of the In2O3, ZnO, SnO2, Y2O3 and Sb2O5 raw material powders is ≥99.995%, and the total content of heavy metal impurities in the powders is less than 8ppm.

[0013] Secondly, the present invention provides a method for preparing the above-mentioned yttrium-antimony co-doped IZTO sputtering target, comprising the following steps: Step S1: Mix ZnO powder with deionized water and zirconium citrate dispersant, mill, filter, and dry to obtain Zr-coated powder. 4+ Modified ZnO powder; the coating layer can delay the decomposition of ZnO during the subsequent sintering heating stage, thereby reducing the amount of zinc volatilization; Step S2: The modified ZnO powder obtained in step S1 is mixed with deionized water and polyethylene glycol dispersant and milled to obtain a ZnO-based slurry. In2O3 powder and SnO2 powder are added sequentially to the ZnO-based slurry for multi-stage milling. Finally, Y2O3 powder and Sb2O5 powder are added for ultrafine grinding to obtain a mixed slurry. A binder is added to the mixed slurry to adjust the solid content to 62 wt.%~68 wt.%. Step S3: Spray granulation of the mixed slurry obtained in step S2 to obtain spherical granulated powder, followed by cold isostatic pressing to obtain a green body; Step S4: Place the green body obtained in step S3 into an atmosphere sintering furnace and perform segmented temperature-controlled sintering in the following three stages: First stage: Heat from room temperature to 650℃ at a rate of 40℃ / h, oxygen partial pressure of 500Pa, and hold for 4h. Second stage: The temperature is raised from 650℃ to 1250℃ at a rate of 25℃ / h, the oxygen partial pressure is 80Pa~120Pa, and the temperature is held for 6h. The third stage: the temperature is raised from 1250℃ to 1580℃ at a rate of 18℃ / h, the oxygen partial pressure is 8000Pa~12000Pa, and the temperature is held for 12h. Step S5: After sintering, the material is cooled and then post-processed to obtain the finished target material.

[0014] Furthermore, in step S1, the sand milling time is 4 hours and the drying temperature is 70℃~90℃.

[0015] Further, in step S2, the D50 of the particles in the mixed slurry is controlled between 35nm and 60nm, and the particle size range is less than 1.8; the viscosity of the mixed slurry is controlled between 1200mPa·s and 1600mPa·s.

[0016] Furthermore, the adhesive mentioned in step S2 is a PVA adhesive.

[0017] Further, in step S3, the inlet air temperature of the spray granulation is 210°C and the outlet air temperature is 85°C, and the flowability of the resulting spherical granulated powder is 22s / 50g~28s / 50g; the pressure of the cold isostatic pressing is 270MPa, the holding time is 30min, and the relative density of the resulting green body is 74%~77%.

[0018] Furthermore, in step S5, the cooling rate is 30℃ / h, and the product is removed from the furnace after cooling to 400℃.

[0019] The present invention achieves its technical effect based on the following three core technical principles. (1) In the crystal structure of IZTO, oxygen vacancies are the key defects affecting the electrical properties and stability of thin films. 3+ The ionic radius is greater than that of In 3+ and Zn 2+ Y 3+ After doping into the crystal lattice, it can replace the corresponding cation sites in the lattice, producing local lattice distortion. This distortion can effectively block the migration and accumulation channels of oxygen vacancies along the lattice, thereby reducing the concentration of mobile oxygen vacancies in the lattice. Simultaneously, high-valence Sb... 5+ Substitution of Sn within the lattice 4+ At this time, additional free electrons are provided to the crystal lattice. These surplus electrons can compensate for the carrier losses that may occur due to lattice distortion and defect scattering, thus maintaining the overall carrier concentration of the material at an appropriate level. 3+ The "oxygen barrier" effect of Sb 5+The “electronic compensation” effect works together to reduce the concentration of lattice defects, thereby improving the lattice quality without using scarce gallium oxide, and significantly reducing the overall cost of raw materials. (2) This invention divides the sintering process into three independent stages, with clear division of functions in each stage. In the first stage, the oxygen partial pressure is controlled at 500 Pa and the temperature is maintained for 4 hours, with the aim of fully decomposing and completely escaping the organic binder. If the binder is not completely decomposed, the residual carbon elements will enter the lattice to form carbon impurity defects, which will seriously affect the conductivity of the target material. In this stage, the degreasing is ensured by setting a reasonable holding time and oxygen partial pressure. In the second stage, the furnace is controlled to a low oxygen partial pressure closed environment of 80 Pa to 120 Pa. In this closed system, although ZnO has a tendency to decompose at high temperature, the zinc vapor and oxygen produced by the decomposition cannot diffuse and escape outside the furnace, forming a local high concentration atmosphere near the surface of the target material. The diffusion rate and escape kinetic energy of zinc vapor are significantly suppressed, combined with Zr 4+ The physical barrier effect of the coating layer locks the zinc element inside the billet, thereby significantly reducing the net volatilization loss of Zn. Through the above-mentioned kinetic inhibition mechanism in a closed low-oxygen environment, the high-temperature decomposition and volatilization of ZnO is effectively controlled. In the third stage, pure oxygen is introduced into the furnace to raise the oxygen partial pressure to a high-oxygen environment of 8000Pa~12000Pa. Under this oxygen-rich condition, the high-concentration oxygen atmosphere can replenish oxygen atoms in the lattice and fill the existing oxygen vacancies; at the same time, the slow heating (18℃ / h) limits the migration rate of the grain boundaries and avoids abnormal grain growth; in addition, the high oxygen partial pressure helps the surface diffusion of oxide particles, promotes the discharge of pores, and achieves high densification of the target material. (3) The present invention pre-coats ZnO powder with Zr. 4+ The powder is modified and then sequentially fed into In₂O₃, SnO₂, and doped oxides for multi-stage milling. This step-by-step feeding method avoids excessive mixing and cross-contamination of different powders in the initial stage, ensuring that each powder reaches the target particle size under its own suitable grinding conditions. Specifically, ZnO is milled alone for 4 hours to ensure sufficient dispersion and avoid subsequent segregation caused by agglomeration; after adding In₂O₃ and SnO₂, it is milled thoroughly to ensure that the three main oxides are fully mixed and uniform; finally, Y₂O₃ and Sb₂O₅ are added for ultrafine milling, which ensures that the doped elements are uniformly attached to the surface of the main oxide particles, which is beneficial to the uniform diffusion of the doped elements during sintering. Through the above-mentioned step-by-step dispersion process, the deviation of the In, Zn, and Sn atomic composition of the finished target material is controlled within ±0.3 at.%. In addition, during the step-by-step milling process, the wear of the milling media and the milling temperature are strictly controlled to ensure that the phase purity and particle size distribution of ZnO are not substantially affected by the long-term milling.

[0020] The function of each raw material component is explained below.

[0021] In₂O₃ (indium oxide): One of the main components constituting the target matrix. 3+ The 5s orbital provides a continuous electron transport channel and is a key element for ensuring high carrier mobility in thin films. If the In content is too low, the electron transport channel is incomplete, and the mobility will decrease significantly; if the In content is too high, the raw material cost will increase significantly and the improvement will be limited. This invention controls the In content within the range of 22 at.% to 26 at.%, achieving an optimal balance between performance and cost.

[0022] ZnO (zinc oxide): One of the main components constituting the target matrix. 2+ The carrier concentration and optical band gap of the target material can be adjusted to improve the light transmittance and film formation properties of the thin film. However, Zn has significant volatility at high temperatures. This invention effectively suppresses the volatilization loss of Zn through a dual approach of surface coating pretreatment and medium-temperature low-oxygen partial pressure closed sintering.

[0023] SnO2 (tin oxide): One of the main components constituting the target matrix. 4+ Through the 5s orbital overlap effect and In 3+ The addition of SnO2 synergistically enhances electron mobility, while also improving the density and chemical stability of the target material. Too low a Sn content weakens the overlapping effect, while too high a content can easily cause local segregation.

[0024] Y₂O₃ (yttrium oxide): One of the doping elements. 3+ The ionic radius is greater than that of In 3+ and Zn 2+ Y 3+ After doping into the crystal lattice, it can replace the relevant cation sites in the crystal lattice, produce local lattice distortion, effectively block the oxygen vacancy generation channel, and is the core component for reducing the oxygen vacancy concentration inside the target material.

[0025] Sb₂O₅ (antimony pentoxide): One of the doping elements. High valence state Sb 5+ Substitution of Sn within the lattice 4+ The excess free electrons are then provided to compensate for the trace carrier loss introduced by Y doping, forming a synergistic doping effect of "oxygen barrier + charge replenishment" with Y.

[0026] Beneficial effects (1) Y 3+ Lattice site occupancy distortion effect and Sb 5+The electronic compensation effect works in conjunction with the oxygen-rich atmosphere of the high-temperature dense oxygen-supplementing section in the three-stage sintering process to achieve dual suppression of oxygen vacancies. The IZTO thin-film transistors prepared by magnetron sputtering using the target material of this invention exhibit significantly improved saturation mobility compared to thin films prepared with conventional IZTO targets, and a substantial reduction in threshold voltage drift under 3600s illumination negative bias testing. This means that in high-end display applications such as ultra-high resolution (e.g., 8K and above) AMOLED, pixel arrays prepared using the target material of this invention can maintain stable switching characteristics under prolonged high-brightness operation, effectively avoiding brightness unevenness and image retention issues caused by threshold drift.

[0027] (2) This invention achieves high densification using only a segmented sintering process under normal pressure, without the need for expensive hot isostatic pressing equipment. The finished target material achieves a high relative density, and the closed porosity inside the blank is extremely low. During magnetron sputtering, residual pores inside the target material are the main cause of arc discharge and large particle sputtering. This invention eliminates pores, making the sputtering process stable and arc-free, significantly reducing the number of pinhole defects on the thin film surface, and significantly improving the production yield of display panels and perovskite battery devices.

[0028] (3) The present invention coats Zr on the surface of ZnO powder. 4+ The synergistic effect of pretreatment and the medium-temperature, low-oxygen partial pressure, closed-loop zinc-locking process (second-stage sintering) effectively suppresses zinc volatilization loss. The surface coating acts as a physical barrier during the heating stage, delaying ZnO decomposition; the medium-temperature, low-oxygen partial pressure, closed-loop environment inhibits the outward diffusion of zinc vapor, reducing net zinc volatilization. The combined effect of these two processes significantly reduces overall zinc volatilization loss during sintering, greatly improving the utilization rate of the powder raw materials. Simultaneously, this invention eliminates the need for a high-valence gallium oxide doping system, significantly reducing raw material costs and enabling continuous mass production of large-size targets.

[0029] (4) Gradient slow heating combined with segmented atmosphere control ensures that the grains remain under control throughout the growth process. The slow heating in the low-temperature degreasing section avoids the violent exothermic reaction during degreasing; the closed low-oxygen environment in the medium-temperature zinc-locking section slows down the grain boundary migration rate; and the ultra-slow heating in the high-temperature oxygen-supplementing section further restricts abnormal grain growth. Ultimately, the average grain size of the target material is controlled within a narrow range, and there are no abnormally large grains. The uniform grain structure results in a uniform conductive path, significantly reducing the sheet resistance difference of sputtered films in different areas of the same target material, and significantly reducing the performance dispersion of devices from different production batches, fully meeting the quality requirements of high-end panel continuous coating production lines.

[0030] (5) The entire sintering process can achieve all functions using only a conventional atmosphere sintering furnace, without the need for special equipment such as a vacuum system or high-pressure devices. The degreasing stage adopts a reasonable heating regime and oxygen partial pressure control, which can completely decompose the organic binder into CO2 and H2O and completely escape, without residual carbon contaminating the target material. Thermogravimetric analysis confirmed that the residual carbon content was less than 10ppm under the condition of holding at 650℃ for 4h. This eliminates the need for plasma oxygen replenishment pretreatment of the target material before coating, and also reduces the overall energy consumption of the production line, which has good industrialization and promotion value. Detailed Implementation

[0031] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0032] This invention provides a low-oxygen-vacancy, high-density yttrium-antimony co-doped IZTO sputtering target. Its matrix is ​​composed of a ternary oxide of In₂O₃, ZnO, and SnO₂, and is doped with Y₂O₃ and Sb₂O₅. In terms of atomic percentage, the target contains 22 at.%~26 at.%, Zn 52 at.%~58 at.%, and Sn 18 at.%~22 at.%, with the sum of In, Zn, and Sn being 100 at.%. Based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.2 at.%~0.7 at.%, and the atomic percentage of Sb is 0.2 at.%~0.5 at.%, with the sum of the atomic percentages of Y and Sb being 0.4 at.%~1.2 at.%. The purity of the raw material powders In2O3, ZnO, SnO2, Y2O3 and Sb2O5 is not less than 99.995%, and the total content of heavy metal impurities in the powder is less than 8 ppm.

[0033] The preparation method of the above-mentioned target material includes the following steps. Each step is described in detail below.

[0034] Step S1: Zinc oxide surface coating pretreatment High-purity ZnO powder was mixed with deionized water and zirconium citrate dispersant in a certain proportion, and then milled in a horizontal sand mill for 4 hours. After milling, the mixture was filtered, and the filter residue was dried at a low temperature of 70-90℃ to obtain Zr-coated surface. 4+ Modified ZnO powder.

[0035] The purpose of this step is to: dissolve the Zr in the zirconium citrate dispersant. 4+ Adsorption and chemical bonding on the surface of ZnO particles form a thin and dense Zr layer.4+ The coating layer acts as a physical barrier during the subsequent sintering heating process, which can delay the decomposition temperature of ZnO and reduce the volatilization rate of zinc.

[0036] Step S2: Grading and Stepwise Wet Pulping This step adopts a graded and step-by-step feeding and grinding approach, and the specific operation is as follows.

[0037] First, the modified ZnO powder obtained in step S1 is mixed with deionized water and polyethylene glycol dispersant, and then milled in a sand mill for 12 hours to obtain a uniformly dispersed ZnO-based slurry. The purpose of milling ZnO alone for a long time is to ensure that it is fully de-agglomerated and to avoid localized zinc-rich areas caused by ZnO particle agglomeration.

[0038] Next, In2O3 and SnO2 powders were added sequentially to the ZnO-based slurry, and multi-stage sand milling was performed for 18 hours. Multi-stage sand milling refers to using multiple sand mills connected in series, with each mill filled with grinding media of different particle sizes (e.g., using 0.8mm, 0.5mm, and 0.3mm zirconium beads sequentially), so that the powder particle size is gradually refined as the slurry passes through each stage, ultimately achieving uniform dispersion at the submicron or even nanometer level.

[0039] Then, Y₂O₃ and Sb₂O₅ powders were added to the above mixed slurry, and ultrafine milling was performed for 6 hours. The dopant element powders were added and ultrafine ground in the final stage to ensure that the Y₂O₃ powder was finely milled. 3+ and Sb 5+ It can be uniformly attached to the surface of the main oxide particles, which is beneficial to the uniform diffusion of dopant elements in the lattice during subsequent sintering.

[0040] After the above grinding process, the D50 of the solid particles in the mixed slurry is controlled within the range of 35nm to 60nm, and the particle size span (calculated by the formula (D90-D10) / D50) is less than 1.8. The smaller the particle size span, the more concentrated the particle size distribution of the powder. This is of great significance for the uniform growth of grains during the subsequent sintering process. A concentrated particle size distribution means that the sintering activity of the particles is similar, and they can be densified synchronously, avoiding the local abnormal grain growth caused by some small particles densifying first while large particles remain in a loose state.

[0041] Finally, PVA (polyvinyl alcohol) binder is added to the mixed slurry to adjust the solid content to 62wt.%~68wt.%, while controlling the slurry viscosity at 1200mPa·s~1600mPa·s. Matching and controlling the solid content and viscosity is a prerequisite for ensuring the subsequent spray granulation effect: too low a solid content will result in insufficient strength of the granulated powder, while too high a solid content will lead to poor slurry flowability, which is detrimental to conveying and atomization.

[0042] Step S3: Spray granulation and cold isostatic pressing The slurry obtained in step S2 is fed into a centrifugal spray drying tower for spray granulation. The inlet air temperature is set to 210℃ and the outlet air temperature is set to 85℃. During the spray drying process, the slurry is atomized into fine droplets, and the water in the droplets evaporates rapidly in the hot air to obtain spherical granulated powder particles. The spherical granulated powder has good flowability, with a flowability index of 22s / 50g~28s / 50g, which facilitates subsequent automatic mold loading and mold cavity filling.

[0043] The granulated powder is filled into a rubber mold and cold isostatically pressed at 270 MPa for 30 minutes to obtain a green body. The cold isostatic pressing technology transmits pressure uniformly through a liquid medium, so that the granulated powder is subjected to equal pressing force in all directions. Therefore, the resulting green body has a uniform density distribution and a relative density of 74% to 77%, which provides a uniform density green body foundation for subsequent high-temperature sintering.

[0044] Step S4: Three-stage gradient oxygen partial pressure temperature-controlled sintering The green body obtained in step S3 is placed in an atmosphere-controlled sintering furnace and sintered in three stages.

[0045] The first stage involves heating from room temperature to 650℃ at a rate of 40℃ / h, with the oxygen partial pressure inside the furnace controlled at 500Pa. After reaching 650℃, the temperature is held for 4 hours. The purpose of this stage is to ensure the complete decomposition and release of the PVA binder. If the heating rate is too fast, the gases produced by the binder decomposition will not have enough time to escape, leading to cracking of the green body. If the oxygen partial pressure is too high or too low, it may affect the composition and escape path of the decomposition products. Experimental optimization has shown that a heating rate of 40℃ / h and an oxygen partial pressure of 500Pa ensure the complete decomposition of the binder into CO2 and H2O, preventing residual carbon from introducing lattice defects.

[0046] The second stage involves heating from 650℃ to 1250℃ at a rate of 25℃ / h, maintaining a low oxygen partial pressure (80Pa~120Pa) in a sealed environment within the furnace. After reaching 1250℃, the temperature is held for 6 hours. This stage corresponds to the temperature range of intense ZnO decomposition (800~1300℃). In this sealed system, although ZnO tends to decompose at high temperatures, the zinc vapor and oxygen produced cannot diffuse out of the furnace, forming a locally high-concentration atmosphere near the target surface. The diffusion rate and escape kinetic energy of zinc vapor are significantly suppressed, combined with the Zr... 4+ The physical barrier effect of the coating layer locks zinc inside the billet, thereby significantly reducing the net volatilization loss of Zn.

[0047] The third stage involves heating from 1250℃ to 1580℃ at a rate of 18℃ / h, while introducing pure oxygen into the furnace to maintain an oxygen-rich atmosphere with an oxygen partial pressure of 8000Pa~12000Pa. After reaching 1580℃, the temperature is held for 12 hours. This stage serves a dual function of densification and oxygen replenishment. On one hand, the high temperature of 1580℃ provides sufficient energy for adequate mass migration of the oxide particles, gradually expelling pores between particles and achieving high densification of the target material. On the other hand, the high concentration of oxygen molecules in the oxygen-rich atmosphere dissociates into oxygen atoms at high temperatures. These oxygen atoms diffuse into the crystal lattice to fill oxygen vacancies, reducing the oxygen vacancy concentration. The slow heating rate of 18℃ / h limits the grain boundary migration rate, effectively preventing abnormal grain growth.

[0048] After sintering, the target material is cooled to 400°C at a constant rate of 30°C / h before being removed from the furnace. The purpose of slow cooling is to avoid microcracks inside the target material due to excessive thermal stress. After being removed from the furnace, the target material is ground to the specified dimensions and surface roughness, and then bonded with a copper metal backing plate to obtain the finished IZTO target material.

[0049] The technical effects of the present invention will be further illustrated below through specific embodiments and comparative examples.

[0050] Example 1

[0051] Target composition: In atomic percentage, In is 24 at.%, Zn is 55 at.%, Sn is 20 at.%, and the sum of the three is 100 at.%; based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.45 at.% and the atomic percentage of Sb is 0.3 at.%.

[0052] Raw material purity: The purity of In2O3, ZnO, SnO2, Y2O3 and Sb2O5 is 99.995%.

[0053] The preparation method includes the following steps: S1: ZnO powder with a purity of 99.995% is mixed with deionized water and zirconium citrate dispersant, horizontally milled for 4 hours, filtered, and dried at a low temperature of 70~90℃ to obtain Zr-coated surface. 4+ Modified ZnO powder; S2: The modified ZnO powder obtained in step S1 is mixed with deionized water and polyethylene glycol dispersant and milled for 12 hours to obtain a ZnO-based slurry. In2O3 and SnO2 powders are added sequentially to the ZnO-based slurry, and the mixture is milled in multiple stages for 18 hours. Y2O3 and Sb2O5 powders are then added to the slurry and milled for 6 hours to obtain a mixed slurry. The D50 of the particles in the mixed slurry is controlled at 50 nm, and the particle size distribution is less than 1.8. A PVA binder is added to the mixed slurry to adjust the solid content to 65 wt.%, and the slurry viscosity is controlled at 1500 mPa·s. S3: The slurry obtained in step S2 is centrifuged and spray-granulated with an inlet air temperature of 210℃ and an outlet air temperature of 85℃ to prepare spherical granulated powder with a powder flowability of 28s / 50g. The granulated powder is filled into a mold and cold isostatically pressed at 270MPa for 30 minutes to form a green body with a relative density of 75%. S4: Place the green body obtained in step S3 into an atmosphere sintering furnace and perform three-stage sintering in sequence: The temperature was raised from room temperature to 650℃ at a rate of 40℃ / h, with an oxygen partial pressure of 500Pa, and held for 4h. The temperature was increased from 650℃ to 1250℃ at a rate of 25℃ / h, the oxygen partial pressure was 100Pa, and the temperature was held for 6h. The temperature was raised from 1250℃ to 1580℃ at a rate of 18℃ / h, and pure oxygen was introduced to maintain an oxygen partial pressure of 10000Pa for 12h. After sintering, the temperature is uniformly reduced to 400℃ at a rate of 30℃ / h before being removed from the furnace. After grinding and bonding with a copper metal backing plate, the finished IZTO sputtering target is obtained.

[0054] Performance test results: The target material has a relative density of 99.72%, an internal closed porosity of 0.08% (measured by Archimedes' displacement method), an average grain size of 2.1 μm, and an oxygen vacancy concentration of 1.8 × 10⁻⁶. 16 cm -3 Zinc volatilization loss was 2.6%. The mobility of a 15nm thick IZTO thin-film TFT sputtered to a depth of 49.7cm was achieved. 2 / V·s, light threshold drift 0.12V, thin film sheet resistance range 2.9%.

[0055] Example 2

[0056] Target composition: In atomic percentage, In is 22 at.%, Zn is 58 at.%, Sn is 19 at.%, and the sum of the three is 100 at.%; based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.2 at.% and the atomic percentage of Sb is 0.2 at.%.

[0057] The preparation method is the same as in Example 1.

[0058] Performance test results: Target relative density 99.58%, internal closed porosity 0.12%, oxygen vacancy concentration 2.0 × 10⁻⁶. 16 cm -3 The film mobility is 45.3 cm⁻¹. 2 / V·s, threshold drift 0.14V, zinc volatilization loss 3.1%.

[0059] Example 3

[0060] Target composition: In atomic percentage, In is 26 at.%, Zn is 52 at.%, Sn is 22 at.%, and the sum of the three is 100 at.%; based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.7 at.% and the atomic percentage of Sb is 0.5 at.%.

[0061] The preparation method is the same as in Example 1.

[0062] Performance test results: Target relative density 99.65%, internal closed porosity 0.10%, oxygen vacancy concentration 2.1×10⁻⁶. 16 cm -3 The film mobility is 51.8 cm⁻¹. 2 / V·s, threshold drift 0.13V.

[0063] Comparative Example 1 This comparative example uses a conventional undoped air-sintered IZTO target.

[0064] Target composition: Composed only of In2O3, ZnO, and SnO2, without the addition of Y2O3 and Sb2O5. The metal atom ratio is the same as in Example 1.

[0065] Preparation method: No doped oxides are added, and the entire process is completed in one sintering at 1580℃ under normal air pressure, without segmented temperature and oxygen control measures.

[0066] Performance test results: Target relative density 96.1%, internal closed porosity 1.8%, oxygen vacancy concentration 6.7 × 10⁻⁶. 16 cm -3 Zinc volatilization loss was 10.8%. TFT thin film mobility was 31.2 cm⁻¹. 2 / V·s, light threshold drift 1.15V, thin film sheet resistance range 12.3%.

[0067] Comparative Example 2 This comparative example uses a single Ga-doped IZTO target, which is a commonly used improvement scheme in existing technologies.

[0068] Target composition: Based on the total atomic percentage of In, Zn and Sn, 0.7 at.% gallium oxide (Ga2O3) is doped, without adding Y and Sb, and the rest of the composition is the same as in Example 1.

[0069] Preparation method: The same wet forming process as in Example 1 was used, but the oxygen partial pressure was not controlled in stages during the sintering process, and the sintering was completed under a single atmosphere condition throughout the process.

[0070] Performance test results: target relative density 97.3%, internal closed porosity 0.9%, thin film migration 37.5 cm. 2 / V·s, the raw material cost is higher than that of Example 1, the threshold drift is 0.78V, and all performance aspects are inferior to those of the present invention.

[0071] Analysis of the test results of the examples and comparative examples shows that: (1) The relative density of the target material in each example of the present invention reaches more than 99.58%, with the best example 1 reaching 99.72%. Comparative example 1 is only 96.1%, and comparative example 2 is 97.3%. The density of both comparative examples failed to break through the 98% threshold, indicating that conventional one-time sintering and single doping schemes cannot effectively eliminate the pores inside the blank. The three-stage sintering process of the present invention, through the stepwise advancement of low-temperature slow degreasing, medium-temperature closed zinc locking, and high-temperature oxygen-rich densification, allows the pores to be fully eliminated in the later stage of sintering, thereby achieving high densification close to the theoretical density. (2) The oxygen vacancy concentration of example 1 (1.8×10) 16 cm -3 ) is only for comparative example 1 (6.7 × 10 16 cm -3 The zinc volatilization loss (2.6%) was only 27% of that of the control group (10.8%), while the zinc volatilization loss (2.6%) was only 24% of that of the control group (10.8%). This significant improvement in both figures is attributed to Y... 3+ Occupying relevant cation sites in the crystal lattice generates localized distortion, blocking oxygen vacancy migration and Sb 5+ Replace Sn 4+ It provides the simultaneous effect of four mechanisms: electronic compensation, suppression of zinc vapor escape behavior in a medium-temperature sealed environment, and replenishment of lattice oxygen in a high-temperature oxygen-rich atmosphere. Neither single doping nor single atmosphere control can simultaneously achieve these two improvements. (3) The film mobility of each embodiment of the present invention is 45.3~51.8 cm. 2 / V·s, significantly better than the 31.2cm of Comparative Example 1. 2 / V·s and 37.5cm in Comparative Example 2 2 / V·s. In terms of illumination threshold drift, Examples 1-3 are 0.12-0.14V, which is far better than Comparative Example 1's 1.15V and Comparative Example 2's 0.78V. In terms of sheet resistance difference, Example 1 is 2.9%, while Comparative Example 1 is as high as 12.3%. These data show that the thin film prepared by the target material of the present invention has significant advantages in three aspects: carrier transport efficiency, long-term working stability and full-area electrical consistency. (4) Although the Ga doping scheme used in Comparative Example 2 improves the performance to a certain extent, its raw material cost is higher than that of Example 1, and the various performance indicators are still significantly inferior to those of the embodiments of the present invention. The present invention uses Y and Sb to replace Ga as doping elements, achieving a significant reduction in cost under the premise of better performance.

[0072] In summary, this invention utilizes Y 3+ -Sb 5+The synergistic effect of three core technologies—co-doping lattice manipulation, three-stage sintering, and hierarchical wet dispersion combined with ZnO surface coating pretreatment—solves three interconnected technical challenges in IZTO targets: oxygen vacancy enrichment, high zinc volatilization loss, and grain coarsening. Experimental data show that the target obtained by this invention has a relative density of no less than 99.6%, an internal porosity of no more than 0.15%, an average grain size controlled between 1.2 μm and 3.5 μm, a lattice oxygen vacancy concentration far lower than that of Comparative Example 1, and a sputtered film mobility of no less than 45 cm⁻¹. 2 / V·s, the threshold voltage drift under negative bias and illumination for 3600s does not exceed 0.15V. Compared with existing technologies, this invention has achieved significant progress in target density, thin film mobility, device stability, electrical consistency, and raw material cost. Furthermore, this invention can achieve all processes using only a conventional atmosphere sintering furnace, eliminating the need for specialized equipment such as hot isostatic pressing. It boasts strong process compatibility, low energy consumption, and can meet the industrial mass production needs of large-size targets. It has broad application prospects in ultra-high resolution (e.g., 8K and above) high-brush-rate AMOLED thin-film transistors and transparent conductive layers for perovskite tandem solar cells.

[0073] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention in any way. All equivalent transformations or modifications made in accordance with the essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. A yttrium-antimony co-doped IZTO sputtering target, characterized in that, The matrix of the target material is composed of ternary oxides In2O3, ZnO and SnO2, and is doped with Y2O3 and Sb2O5; In terms of atomic percentage, the target material contains 22 at.%~26 at.%, 52 at.%~58 at.%, and 18 at.%~22 at.%, with the sum of In, Zn, and Sn being 100 at.%. Based on the total atomic percentage of In, Zn, and Sn, the atomic percentage of Y is 0.2 at.% to 0.7 at.%, the atomic percentage of Sb is 0.2 at.% to 0.5 at.%, and the sum of the atomic percentages of Y and Sb is 0.4 at.% to 1.2 at.%.

2. The yttrium-antimony co-doped IZTO sputtering target according to claim 1, characterized in that, In terms of atomic percentage, the target material contains 24 at.%, 55 at.%, and 20 at.%, with the sum of the three being 100 at.%; based on the total atomic percentage of the three, the atomic percentage of Y is 0.45 at.% and the atomic percentage of Sb is 0.3 at.%.

3. The yttrium-antimony co-doped IZTO sputtering target according to claim 1, characterized in that, The target material meets the following microstructure and performance indicators: relative theoretical density ≥ 99.6%, internal closed porosity ≤ 0.15%, average grain size of 1.2 μm to 3.5 μm, and lattice oxygen vacancy concentration. Furthermore, the atomic composition fluctuations of In, Zn, and Sn across the entire target area do not exceed ±0.3 at.%.

4. The yttrium-antimony co-doped IZTO sputtering target according to claim 1, characterized in that, The purity of the In2O3, ZnO, SnO2, Y2O3 and Sb2O5 raw material powders is ≥99.995%, and the total content of heavy metal impurities in the powders is less than 8ppm.

5. A method for preparing a yttrium-antimony co-doped IZTO sputtering target as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Step S1: Mix ZnO powder with deionized water and zirconium citrate dispersant, mill, filter, and dry to obtain Zr-coated powder. 4+ Modified ZnO powder; Step S2: The modified ZnO powder obtained in step S1 is mixed with deionized water and polyethylene glycol dispersant and then milled to obtain a ZnO-based slurry. In₂O₃ powder and SnO₂ powder are added sequentially to the ZnO-based slurry for multi-stage milling. Finally, Y₂O₃ powder and Sb₂O₅ powder are added for ultrafine grinding to obtain a mixed slurry. A binder is added to the mixed slurry to adjust the solid content to 62 wt.%~68 wt.%. Step S3: Spray granulation of the mixed slurry obtained in step S2 to obtain spherical granulated powder, followed by cold isostatic pressing to obtain a green body; Step S4: Place the green body obtained in step S3 into an atmosphere sintering furnace and perform segmented temperature-controlled sintering in the following three stages: First stage: Heat from room temperature to 650℃ at a rate of 40℃ / h, oxygen partial pressure of 500Pa, and hold for 4h. Second stage: The temperature is raised from 650℃ to 1250℃ at a rate of 25℃ / h, the oxygen partial pressure is 80Pa~120Pa, and the temperature is held for 6h. The third stage: the temperature is raised from 1250℃ to 1580℃ at a rate of 18℃ / h, the oxygen partial pressure is 8000Pa~12000Pa, and the temperature is held for 12h. Step S5: After sintering, the material is cooled and then post-processed to obtain the finished target material.

6. The preparation method according to claim 5, characterized in that, In step S1, the sand milling time is 4 hours and the drying temperature is 70℃~90℃.

7. The preparation method according to claim 5, characterized in that, In step S2, the D50 of the particles in the mixed slurry is controlled between 35nm and 60nm, and the particle size range is less than 1.8; the viscosity of the mixed slurry is controlled between 1200mPa·s and 1600mPa·s.

8. The preparation method according to claim 5, characterized in that, The adhesive mentioned in step S2 is a PVA adhesive.

9. The preparation method according to claim 5, characterized in that, In step S3, the inlet air temperature of the spray granulation is 210℃ and the outlet air temperature is 85℃, and the flowability of the resulting spherical granulated powder is 22s / 50g~28s / 50g; the pressure of the cold isostatic pressing is 270MPa, the holding time is 30min, and the relative density of the resulting green body is 74%~77%.

10. The preparation method according to claim 5, characterized in that, In step S5, the cooling rate is 30℃ / h, and the furnace is removed after the temperature drops to 400℃.